Chiral Structure of Scalar and Pseudoscalar Mesons - Hua-Xing Chen (Advances in High Energy Physics)
We systematically study the chiral structure of local tetraquark currents of flavor singlet and JP=0+. We also investigate their chiral partners, including scalar and pseudoscalar tetraquark currents of flavor singlet, octet, 10, 10¯, and 27. We study their chiral transformation properties. Particularly, we use the tetraquark currents belonging to the “nonexotic” [(3-,3)⊕(3,3-)] chiral multiplets to calculate the masses of light scalar mesons through QCD sum rule. The two-point correlation functions are calculated including all terms and only the connected parts (Weinberg (2013), Coleman (1985), and Page (2003)). The results are consistent with the experimental values.